Hyperhidrosis: disease aetiology, classification and management in the light of modern treatment modalities - Kisielnicka, Anna; Szczerkowska-Dobosz, Aneta; Purzycka-Bohdan, Dorota; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Hyperhidrosis is a disorder of sweat glands characterized by overproduction of sweat, which is inadequate to the thermoregulatory needs of the body system. Owing to the heavy social and economic burden of the disproportionate perspiration, current treatment methods still do not seem to be sufficient enough to reach patients’ expectations. Therefore, the researchers continue a robust pursuit of novel therapy modalities such as topical treatment methods, oral agents, minimally-invasive medical approach and surgical techniques. In this review article authors summarise the disease outline with the emphasis on the new era of hyperhidrosis treatment methods.